Adaptive control of time delay teleoperation system with uncertain dynamics - Lu, Siyu; Ban, Yuxi; Zhang, Xia; Yang, Bo; Liu, Shan; Yin, Lirong; Zheng, Wenfeng (Frontiers in Neurorobotics, 2022)
A bilateral adaptive control method based on PEB control structure is designed for a class of time-delay force feedback teleoperation system without external interference and internal friction to study the uncertainty of dynamic parameters and time delay. The stability and tracking performances of the closed-loop constant time delay teleoperation system are analyzed by Lyapunov stability theory. Finally, the controller designed in this paper is successfully applied to the teleoperation system composed of a two-degree of freedom rotating manipulator as the master robot and the slave robot. The simulation is carried out in no operator and environment force or with operator and environment force. The adaptive bilateral control method's control performance is compared with that of the traditional time-delay teleoperation system. Finally, it is verified that the method has good control performance.